The Socio-Economic Role of Small Agribusiness in the Development of Modern Ukraine and Poland - Shpykuliak, Oleksandr; Balaniuk, Ivan; Shelenko, Diana; Balaniuk, Sergiy; Sukhovii, Alona (Journal of Vasyl Stefanyk Precarpathian National University, 2024)
Factors influencing the formation of the socio-economic role of small agribusiness, directions for establishing the institutional and organizational-economic structure of small-scale enterprises in the agricultural sector of Ukraine and Poland are singled out. An analysis of the activities of small agribusiness entities was carried out using statistical data from GUS (Central Statistical Office of Poland) and the State Statistics Service of Ukraine for the period from 2010 to 2020. The trends in running a craft business were disclosed. It has been demonstrated that the development of the agricultural sector is dominated by the direct freedom of decision-making and choice of producers. It was established that small agribusiness in Ukraine and Poland can meet the requirements of a competitive environment and function effectively under the conditions of coronavirus and war in Ukraine. The purpose of our research is to theoretically and methodologically justify scientific provisions and develop recommendations that will accumulate specific institutional and technological capabilities to produce necessary raw materials and create agri-food products in Ukraine and Poland. The methodological basis of the research includes fundamental principles of economic theory, management, and studies of scholars regarding the socio-economic role of small agribusiness in the conditions of war in Ukraine. Observation, sampling, and grouping methods were used for the theoretical justification in identifying problems in the development of small agricultural businesses; generalization and comparative analysis were employed to form the institutional and organizational-economic functionality of small-scale enterprises in the agricultural sector of Ukraine and rural areas, refine the conceptual framework, and draw conclusions and proposals on the selected topic.